The Menopausal Symptoms of Paramedics at a Tertiary Care Center - Toar A Kumaat; Maria F T Loho; Eddy Suparman (Indonesian Society of Obstetrics and Gynecology, 2017)
Objective: To assess paramedic menopausal symptoms on the inpatient unit and outpatient unit. Methods: This was a cross sectional study. Data collect by fill the questioner, the questioner fill by menopausal paramedic on Prof. Dr. R. D. Kandou Manado Hospital from October 2016 to January 2017. Data were analyzed using SPSS 22.0 for Windows. Results: Of 60 paramedics, 30 were divided to inpatient unit and the other 30 were divided to outpatient unit. By the menopause rating scale, somatic and urogenital complaint in statistical test have no significant differences. Psychology complaint with a moderate complaints on inpatient unit have 19 paramedic (63%) and 12 paramedic (40%) on outpatient paramedic, in statistical have a significant differences (x2=9.62, p=0.022). On the total score menopausal complaints, the moderate complaints 18 paramedic (60%) on the inpatient unit and the minor complaints 21 paramedic (70%) on the outpatient unit, in statistical have a significant differences (x2=6.97, p=0.031). Conclusion: There is no significant difference in somatic and urogenital complaints on paramedic inpatient unit and outpatient unit. There is a significant difference in psychological complaints and total score menopausal complaints on paramedic inpatient unit and outpatient unit. [Indones J Obstet Gynecol 2017; 5-4: 208-212] Keywords: menopause, menopause rating scale, paramedic